2020
DOI: 10.1172/jci140378
|View full text |Cite|
|
Sign up to set email alerts
|

Mass cytometry detects H3.3K27M-specific vaccine responses in diffuse midline glioma

Abstract: CONCLUSION. Administration of the H3.3K27M-specific vaccine was well tolerated. Patients with H3.3K27M-specific CD8 + immunological responses demonstrated prolonged OS compared with nonresponders. TRIAL REGISTRATION. ClinicalTrials.gov NCT02960230.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 52 publications
0
84
0
Order By: Relevance
“…For instance, patients with melanoma with lower levels of circulating M-MDSCs at baseline were significantly more likely to achieve prolonged overall survival following anti-CTLA4 ICI 139 143 . Similarly, in patients with diffuse midline glioma, lower frequencies of M-MDSCs in peripheral blood predict improved response to neoantigen vaccine immunotherapy 144 . Beyond myeloid suppressive cells, a recent study demonstrated that the baseline abundance of a subset of circulating T reg cells defined as CD45RA − FOXP3 hi were predictive of relapse after patients with breast cancer underwent surgery 53 .…”
Section: Systemic Immune Biomarkers For Cancermentioning
confidence: 99%
“…For instance, patients with melanoma with lower levels of circulating M-MDSCs at baseline were significantly more likely to achieve prolonged overall survival following anti-CTLA4 ICI 139 143 . Similarly, in patients with diffuse midline glioma, lower frequencies of M-MDSCs in peripheral blood predict improved response to neoantigen vaccine immunotherapy 144 . Beyond myeloid suppressive cells, a recent study demonstrated that the baseline abundance of a subset of circulating T reg cells defined as CD45RA − FOXP3 hi were predictive of relapse after patients with breast cancer underwent surgery 53 .…”
Section: Systemic Immune Biomarkers For Cancermentioning
confidence: 99%
“…As we can see, the tumor site was not associated with prognosis in our study. Patients with diffuse midline gliomas (DMGs) have dismal outcomes (Mueller and Taitt et al, 2020). Furthermore, DMGs are mainly located in the brainstem in pediatric patients (Mackay and Burford et al, 2017;Mueller and Jain et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients are also often treated with dexamethasone, a synthetic glucocorticoid, for peri-operative control of intracerebral edema and consequent neurological symptoms (e.g., headaches, confusion, weakness, other focal neurological deficits, and seizures). However, dexamethasone and other glucocorticoids significantly dampen the overall immune response and can reduce therapeutic benefit of immunotherapies, resulting in consensus recommendations that their use be minimized prior to and during immunotherapy trials [54][55][56]. For example, it was recently reported that use of dexamethasone hampered vaccine-reactive T cell responses during neoantigen vaccine priming in patients with newly diagnosed malignant glioma [56,57].…”
Section: Suppression Of the Immune Response By Standard Therapy And Cmentioning
confidence: 99%
“…In a recent multicenter pilot study, vaccine targeting H3.3K27M, along with Toll-like receptor 3 agonist, polyinosinicpolycytidylic acid stabilized with polylysine and carboxymethylcellulose (poly-ICLC), was administered to HLA-A02.201+ pediatric patients with H3.3K27M+ diffuse midline glioma (DMG). A subset of patients (n = 18) were selected for available multi-timepoint blood draws and 39% exhibited an expansion of H3.3K27M-reactive CD8 + T cells (mOS 16.3 months) and showed significantly prolonged OS compared to tumors who failed to demonstrate a T cell response (mOS 9.9 months) [56]. Furthermore, dexamethasone administration is inversely associated with H3.3K27M-reactive CD8 + T cell responses [56].…”
Section: Vaccine Therapymentioning
confidence: 99%